DC bus voltage control strategy of PV systems based on fuzzy logic - El Oussoul Laarabi; Elhamdaouy Achour; Belattar Abdellatif; Ait Madi Abdessalam (E3S Web of Conferences)
In a grid-connected photovoltaic (PV) power generation system, sudden changes in the output power of PV panels, caused by fluctuations in solar irradiation or shading, as well as real-time variations in system load, can lead to significant voltage fluctuations in the DC bus. If not properly managed, these voltage fluctuations can compromise the stability and efficiency of the entire system. To address this challenge and improve the performance of DC bus voltage regulation, this paper proposes a control method based on a fuzzy logic controller (FLC). The proposed method primarily relies on two key correctors: the first is an energy corrector, which regulates the energy stored in the DC bus capacitor, and the second is an FLC, which controls the current to maintain voltage stability. This dual-corrector system is designed to enhance the system’s response to power fluctuations and maintain a stable DC bus voltage. The performance of this FLC-based control approach is compared to the traditional double closed-loop PI control method. Simulation results, carried out in the Matlab/Simulink environment, demonstrate that the proposed FLC method outperforms the traditional PI control in terms of both system stability and dynamic response. This improvement is especially evident in handling sudden disturbances and maintaining consistent voltage levels.